2005
DOI: 10.1158/1078-0432.ccr-05-0524
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 Expression in Postmastectomy Chest Wall Relapse

Abstract: Purpose: Cyclooxygenase-2 (COX-2) expression has been shown to be associated with radiation resistance, which theoretically could be overcome with the use of COX-2 inhibitors. The purpose of this study was to assess the prognostic significance and clinical correlations of COX-2 expression (COX) in a cohort of patients treated with radiation for postmastectomy chest wall relapse. Experimental Design: Between 1975 and 1999, 113 patients were treated for isolated postmastectomy chest wall relapse. All patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
2
1
0
Order By: Relevance
“…In the present study we defined a COX-2 positive status only when staining intensity was scored 3, explaining why the detection rate was comparably low with 22.3%. This is similar to Kim and co-workers who regarded a staining intensity of 2 and 3 as positive [ 27 ]. In their study of postmastectomy chest wall relapse, COX-2 protein expression correlated with increased distant metastasis [ 27 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present study we defined a COX-2 positive status only when staining intensity was scored 3, explaining why the detection rate was comparably low with 22.3%. This is similar to Kim and co-workers who regarded a staining intensity of 2 and 3 as positive [ 27 ]. In their study of postmastectomy chest wall relapse, COX-2 protein expression correlated with increased distant metastasis [ 27 ].…”
Section: Discussionsupporting
confidence: 89%
“…This is similar to Kim and co-workers who regarded a staining intensity of 2 and 3 as positive [ 27 ]. In their study of postmastectomy chest wall relapse, COX-2 protein expression correlated with increased distant metastasis [ 27 ]. In line with their findings, several other retrospective studies have reported that increased protein expression of COX-2 is a negative prognostic marker for increased metastasis or reduced overall survival in primary breast cancer [ 9 , 8 , 10 , 11 ].…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, we chose COX‐2, Bcl‐2, and p53 for their prognostic significance for long‐term outcomes. COX‐2 has been associated with aggressive breast cancer and poorer outcomes with respect to higher breast relapse and worse disease‐free and overall survival rates, particularly in estrogen‐dependent tumors (28,31). Bcl‐2 is a protein in the Bcl family associated with apoptosis, and its expression appears to be associated with higher breast recurrence (30,32,33).…”
Section: Discussionmentioning
confidence: 99%